Informal Governance: Comparative Perspectives on Co-optation, Control and Camouflage in Rwanda, Tanzania and Uganda - Claudia Baez Camargo; Lucy Koechlin (Revue Internationale de Politique de Développement)
This article applies a novel conceptual framework to characterise and assess the repertoire of practices used by informal networks to redistribute power and access to resources. These distinct norms and practices are typologised as co-optation, control, and camouflage. Co-optation involves recruitment into the network by means of the reciprocal exchange of favours. Control is about ensuring discipline amongst network members by means of shaming and social isolation. Camouflage refers to the formal facades behind which informality hides and is about protecting and legitimising the network. All three are relevant to a more fine-grained understanding of corruption and its underpinnings. Findings from our comparative research in three East African countries (Rwanda, Tanzania and Uganda) suggest that these informal practices are relevant to an understanding of the choices and attitudes of providers and users of public services at the local level. Adopting this analytical lens helps to explain the limited impact of conventional anti-corruption prescriptions and provides a basis to develop alternative strategies that harness the potential of social network dynamics to promote positive anti-corruption outcomes.